Application of Distraction Watching Cartoons Animation to Reduce Anxiety Level During Injection in Preschool in The Children's HCU Room, Dr. Moewardi Hospital Surakarta - Tina, Nadia Agus; Rasyida, Zulfa Mahdiatur; Ratrinaningsih, Suciana (Al-Hijrah Indonesia, 2025)
Background: Anxiety experienced by preschoolers during hospitalization is an important problem; if not addressed, it can affect the growth and development process. Hospitalization can be a situation that is considered a crisis by the child. This situation arises because children are trying to adapt to a foreign environment, namely, hospitals, which can cause anxiety in children. One of the efforts to overcome anxiety can be done with distraction techniques, one of which is watching animated cartoon films. Objective: to find out the results before and after applying Distraction Watching Animated Cartoons in Reducing Anxiety Levels During Injection in Preschool in the Children's HCU Room of Dr. Moewardi Hospital, Surakarta. Methods: This study used a descriptive method with purposive random sampling and a HAR-S anxiety level measuring tool. Results: The results of the application of 2 respondents carried out for 1 time in 3 days, with a duration of 10 minutes, showed the effect of reducing anxiety in children. Conclusion: There were differences and changes in anxiety levels in the respondents during the application of distractions, such as watching animated cartoons, in reducing anxiety levels during injection.